PENGARUH MODEL PEMBELAJARAN KOOPERATIF TGT BERBANTUAN PERMAINAN LUDO TERHADAP HASIL BELAJAR DI SMK MUHAMMADIYAH 2 PEKANBARU - Uhti Wahidah; Suarman Suarman; Sri Kartikowati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: This research aims to determine the effect of the Teams Games Tournament (TGT) model assisted by ludo game on learning achievement. This research was implemented at SMK Muhammadiyah 2th Pekanbaru. This study is Pre-Experimental Design by using One-Group Pretest-Posttest Design. The population is all of students of 11th grade AK 1 withtotal number of students are 32, all taken as sample. Then the data was analyzed used N-G and paired t Test. The average of N-Gain achievement are known to be in the